Front Cover: Probing the Potential of Hitherto Unexplored Base‐Stabilized Borylenes in Dinitrogen Binding (Chem. Eur. J. 21/2022). Issue 21 (23rd March 2022) - Fantuzzi, Felipe; Moral, Rubi; Dewhurst, Rian D.; Braunschweig, Holger; Phukan, Ashwini K.
Abstract : Despite decades of intense research, metal‐free binding of N2 is still a tantalizing goal. We have computationally explored di‐coordinate, singly base‐stabilized borylenes as candidates for N2 capture. Besides identifying key borylene–N2 adducts with low activation barriers, we reveal that the reaction exergonicity is linearly dependent on the natural charge at boron. These findings pave the way for the design of boron‐based compounds with potential applications in small‐molecule activation. More information can be found in the Research Article by F. Fantuzzi, H. Braunschweig, A. K. Phukan et al. (DOI: 10.1002/chem.202104123 ). Cover designed by F.F.